Endoscopic Diagnosis and Differentiation of Inflammatory Bowel Disease - Ji Min Lee; Kang-Moon Lee (Korean Society of Gastrointestinal Endoscopy, 2016)
Patients with inflammatory bowel disease have significantly increased in recent decades in Korea. Intestinal tuberculosis (ITB) and intestinal Behcet's disease (BD), which should be differentiated from Crohn's disease (CD), are more frequent in Korea than in the West. Thus, the accurate diagnosis of these inflammatory diseases is problematic in Korea and clinicians should fully understand their clinical and endoscopic characteristics. Ulcerative colitis mostly presents with rectal inflammation and continuous lesions, while CD presents with discontinuous inflammatory lesions and frequently involves the ileocecal area. Involvement of fewer than four segments, a patulous ileocecal valve, transverse ulcers, and scars or pseudopolyps are more frequently seen in ITB than in CD. A few ulcers with discrete margins are a typical endoscopic finding of intestinal BD. However, the differential diagnosis is difficult in many clinical situations because typical endoscopic findings are not always observed. Therefore, clinicians should also consider symptoms and laboratory, pathological, and radiological findings, in addition to endoscopic findings.